Semaphorins and Their Receptors in Hematological Malignancies - Wei, Li; Li, Hongbo; Tamagnone, Luca; You, Hua (Frontiers in Oncology, 2019)
While Semaphorins were initially identified as axonal guidance cues for wiring the neural network, it was then recognized their wide relevance in tissue development and homeostasis. Notably, semaphorin activities were also extensively studied in many types of solid tumours; however, their relevance in hematological malignancies is far from understood. In this mini-review, we surveyed the current knowledge about semaphorins and their receptors in leukemias, lymphomas and multiple myeloma. Noteworthy, current data support a promoting role for Semaphorin 4D and Neuropilin-1 in these tumors, while Semaphorin 3A seems to consistently act as oncosuppressor in leukemias and multiple myeloma. The expression levels and functional activities of SEMA3B, SEMA3F and Neuropilin-2 have furthermore been investigated in leukemias and lymphoma cells. Herein, we reviewed the state of the art and highlighted some of the open questions to be addressed in the field.